Estudio de factibilidad de una microempresa dedicada a la venta de alimentos bebidasa base de frutas tropicales en el cantón El Empalme, año 2013 - Solis Vera, Geomary Lisseth (2015)
The city of El Empalme, has in recent years experienced considerable growth in the population, and enjoys a huge trade potential and a great production of tropical fruits, essential to meet project objectives feedstock. At the present time microenterprises are an important productive sector that provides the opportunity to appease unemployment, underemployment and poverty; our country is recognized worldwide for the quality and variety of tropical fruits they produce, it is intended that the micro sells food and tropical fruit drinks located in the city of El Empalme generate working places and economic profitability the investor. The feasibility study for the creation of a small business that sells food and drinks with tropical fruits in the village of El Empalme, Guayas province, it has been programmed according to the technical conditions and requirements of the final product. The purpose of this work is to create a small business on food and drinks to the market town of El Empalme along the lines of a feasibility study, a market survey that allowed analyze the unmet demand, a technical study was first addressed, where the relevant aspects related to the operational process of microenterprise, determining the necessary resources, production plans and detailed shopping. The investigation determined in the analysis of the economic study - I microenterprise finance that is feasible and viable to settle in the village of El Empalme, according to the economic study – financial….